2020
DOI: 10.1155/2020/4106383
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetic Foot Ulcer and Associated Factors among Adult Diabetic Patients on Follow-Up Clinic at Jimma Medical Center, Southwest Ethiopia, 2019: An Institutional-Based Cross-Sectional Study

Abstract: Background. Diabetic foot ulceration is a devastating complication of diabetes mellitus and is a major source of morbidity and mortality. So far, there are few published data on diabetic foot ulcers and its determinants among diabetic patients on follow-up at Jimma Medical Center. Hence, the aim of this study was to assess the prevalence of diabetic foot ulcer and its determinants among patients with diabetes mellitus at Jimma Medical Center. Methods. A hospital-based cross-sectional study was conducted from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
45
2
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 32 publications
7
45
2
9
Order By: Relevance
“…Thus degree of glycemic control not only acts as a major risk factor for developing DFU but also plays a major role for its treatment success rate. Similar findings also documented in few previous studies [13,14] . Current study clearly shows that progression of major complications like DFU can be controlled if patients achieve optimal plasma glucose level.…”
Section: Discussionsupporting
confidence: 92%
“…Thus degree of glycemic control not only acts as a major risk factor for developing DFU but also plays a major role for its treatment success rate. Similar findings also documented in few previous studies [13,14] . Current study clearly shows that progression of major complications like DFU can be controlled if patients achieve optimal plasma glucose level.…”
Section: Discussionsupporting
confidence: 92%
“…In the presence of neuropathy the annual incidence of foot ulceration has demonstrated an approximately 10-fold increase [ 18 ]. A recent study in Jimma showed that the prevalence of foot ulcer in diabetic patients on follow-up at Jimma Medical Center was 11.6% and peripheral neuropathy is one of the major risk factor identified for diabetic foot ulcer [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the results show that respondents with diabetic foot ulcer also have polyneuropathy in a statistically significant percentage (p = 0.010). Abdissa et al state that the connection between these two complications is conditioned by diabetic polyneuropathy, which causes loss of protective feeling of pain, loss of pressure perception and damage to microcirculation ( 33 ). Scientific studies also show that peripheral occlusive disease is a risk factor for the development of these complications in 15% of cases, as well as neuropathic and dystrophic tissue that is particularly susceptible to infections and injuries, especially in the elderly ( 34 - 35 ).…”
Section: Discussionmentioning
confidence: 99%